A clinico-epidemiological profile of patients with influenza A H1N1 attending a tertiary care hospital in southern Rajasthan region of India - Singhal, Yogesh Kumar; Kothari, Nitin (International Journal of Research in Medical Sciences, 2019)
Background: Influenza, commonly referred to as the flu, is an infectious disease caused by RNA viruses of the family Orthomyxoviridae (the influenza viruses). Swine flu cases resurfaced in month of January 2015 in Southern region of India which are continuation of pandemic 2009. Aim of this study is to summaries the clinical and epidemiological factors associated with swine flu as well as to estimate the burden of Influenza A H1N1 (Swine Flu) cases. Methods: A complete data of all the patients visiting swine flu OPDs, swine flu wards and ICU were maintained for year 2015. Each patient visiting either the swine flu OPD or the swine flu ward, who was suspected clinically to be H1N1 positive were tested for real time PCR. Results: Out of 1247 samples tested for rt-PCR 491 (39.37%) cases were identified as positive for H1N1. Maximum swine positivity was seen in the age group of 16-30 year i.e. 147 (29.94%). Overall swine positivity was significantly (<0.001) higher in females than male and extremely statistically significant (p<0.0001) higher in rural areas than urban. Cough was the most common clinical symptoms affecting 469(95.52%) patients followed by fever (92.26%) and breathlessness 402(81.87%). Conclusions: Our study will help epidemiologist and clinician to identify epidemiological factors and clinical picture of swine flu.